2007
DOI: 10.1016/j.ygeno.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Members of a novel gene family, Gsdm, are expressed exclusively in the epithelium of the skin and gastrointestinal tract in a highly tissue-specific manner

Abstract: Gasdermin (Gsdm) was originally identified as a candidate causative gene for several mouse skin mutants. Several Gsdm-related genes sharing a protein domain with DFNA5, the causative gene of human nonsyndromic hearing loss, have been found in the mouse and human genomes, and this group is referred to as the DFNA5-Gasdermin domain family. However, our current comparative genomic analysis identified several novel motifs distinct from the previously reported domain in the Gsdm-related genes. We also identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
241
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(244 citation statements)
references
References 32 publications
3
241
0
Order By: Relevance
“…Although the two families evolved from a common ancestor, phylogenetic analysis has indicated that the two clades are distinct, 24 leaving DFNA5 with only a single closely related protein: PJVK. The first part of PJVK shows high similarity with DFNA5, but does not induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the two families evolved from a common ancestor, phylogenetic analysis has indicated that the two clades are distinct, 24 leaving DFNA5 with only a single closely related protein: PJVK. The first part of PJVK shows high similarity with DFNA5, but does not induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been demonstrated that these genes are expressed in the intestinal epithelium, the function of this subfamily is relatively uncharacterized (Tamura et al, 2007).…”
Section: Characterization Of Nkx22mentioning
confidence: 99%
“…GSDMB (also known as GSDML) is a novel protein that belongs to the gasdermin (GSDM) family that consists of four human genes: GSDMA, GSDMB, GSDMC and GSDMD [17]. A mouse or rat ortholog of the GSDMB gene has not been identified, and it may have evolved independently in humans through a GSDM gene duplication [18].…”
Section: Resultsmentioning
confidence: 99%
“…The human GSDMB gene consists of 12 exons and four different splice variants have been described, which differ in exons 6 and 7 of the GSDMB gene [19]. GSDMB has been linked to cancer progression and is expressed in human gastric, liver, colon and breast cancer cell lines and carcinomas [17,19]. Although several genetic studies show a strong association of GSDMB with asthma, no functional studies to date have investigated the biological role of GSDMB in asthma and related airway cell types.…”
Section: Resultsmentioning
confidence: 99%